Tipe Mating pada Empat Isolat Thanatephorus Cucumeris Anamorf: Rhizoctonia solani) Anastomosis Group (AG) 1-IC - Achmadi Priyatmojo (Jurnal Perlindungan Tanaman Indonesia, 2006)
Four parent isolates (189, Rh28, BW3 and F-1) of Thanatephorus cucumeris (anamorph: Rhizoctonia solani) AG 1-IC were induced to produce basidiospores using soil-over culture method. All of four parent isolates could produce basidiospores. Colonies obtained from single basidiospore isolate of each parent isolate were paired on charcoal potato dextrose agar. Single basidiospore isolate having different mating type produced tuft at area of the junction of paired colonies. On the based of tuft formation, single basidiospore isolates of each parent isolate could be divided into two different mating types, therefore it is concluded that each of 189, Rh28, BW3 and F-1 isolate of T. cucumeris AG I-IC has bipolar mating type.